Computational and Thought Language: Beyond The Searle—Dennet Paradigm - Mukmin, Muhammad Andry; Putri, Luh Gede Saraswati; Manalu, Abby Gina Boang (Jurnal Filsafat "WISDOM", 2025)
This study examines the ontological tension in the debate between John R. Searle and Daniel C. Dennett regarding the relationship between language and consciousness, and then proposes the model of Computational Language and Thought Language as a new analytical framework. Computational Language is understood as a syntactic, algorithm-based language without intentionality. Conversely,Thought Language is a conceptual-intentional expression rooted in phenomenological consciousness. Through a conceptual-critical analysis grounded in the hermeneutic-phenomenological tradition, the study demonstrates that artificial intelligence can only produce Computational Language, whereas Thought Language cannot be reduced to computational operations. Neurocognitive evidence, such as the activation of Broca’s area in syntactic processing, supports the description of Computational Language, while Thought Language remains positioned as an ontological construct beyond empirical verification. This model not only maps the epistemic limits of artificial intelligence but also opens new avenues for reflection in the philosophy of mind, language, and technology.